The effect of heavy versus light load jump squats on strength, power and speed - McBride, J.; Newton, R.; Triplett-McBride, T.; Davie, A.
This investigation indicates that training with light load jump squats results in increased movement velocity capabilities. However, while training with heavy load jump squats increases force and power performance it seems, in an acute situation, to hinder movement velocity and subsequent performance in high velocity activities (ie. jumping, sprinting).